HIV/AIDS: global trends, global funds and delivery bottlenecks - Hadingham Jacqui; Coovadia Hoosen M (Globalization and Health, 2005)
Abstract Globalisation affects all facets of human life, including health and well being. The HIV/AIDS epidemic has highlighted the global nature of human health and welfare and globalisation has given rise to a trend toward finding common solutions to global health challenges. Numerous international funds have been set up in recent times to address global health challenges such as HIV. However, despite increasingly large amounts of funding for health initiatives being made available to poorer regions of the world, HIV infection rates and prevalence continue to increase world wide. As a result, the AIDS epidemic is expanding and intensifying globally. Worst affected are undoubtedly the poorer regions of the world as combinations of poverty, disease, famine, political and economic instability and weak health infrastructure exacerbate the severe and far-reaching impacts of the epidemic. One of the major reasons for the apparent ineffectiveness of global interventions is historical weaknesses in the health systems of underdeveloped countries, which contribute to bottlenecks in the distribution and utilisation of funds. Strengthening these health systems, although a vital component in addressing the global epidemic, must however be accompanied by mitigation of other determinants as well. These are intrinsically complex and include social and environmental factors, sexual behaviour, issues of human rights and biological factors, all of which contribute to HIV transmission, progression and mortality. An equally important factor is ensuring an equitable balance between prevention and treatment programmes in order to holistically address the challenges presented by the epidemic.